The APOS Content Basic Algebra Module to Improve the Learning Autonomy of Achieving Mathematics Connection Skills - Prasetyo, Krisno Budi; Sukestiyarno, YL.; Cahyono, Adi Nur (Unnes Journal of Mathematics Education Research, 2021)
This research aims to develop an APOS content-basic algebra for autonomous learning to achieve the mathematics connection skills that meet the instrument validity and implementation effectiveness criteria. The module included the basic concept of basic algebra as the learning reference for learners. Thus, learners could refer to the materials autonomously. The module was arranged systematically and complemented with detailed stages. They could facilitate the readers to act and to try the process of analogy. A similar stage also occurred on an object, the new problem, to create a theoretical framework in the form of a scheme. This research used a research and development design. The stages were defining the algebraic problems, designing the APOS-based module, creating a product draft, validating the module, and examining the effectiveness. The researcher conducted the field test with the learner representations from primary school, Junior High School, and Vocational High School. The research variables were learning autonomy and mathematics connection skills. The research used questionnaires and tests to collect the data. The data were then analyzed descriptively analytically. The experts' judgment obtained a score of 4.08, with a valid criterion. Then, the product was tested for the learners’ representations. The results showed their learning autonomy achieved scores of 73 (the primary school learner), 75 (the JHS learners), and 81 (the VHS learners). On the other hand, the mathematics connection skill scores were 75 (the primary school learner), 80 (the JHS learners), and 85 (the VHS learners) It showed that learning with the APOS content module had positive responses and achieved the expected results (effective).